2023
DOI: 10.1111/cns.14058
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcomes of tirofiban after endovascular treatment in acute ischemic stroke: Experience from a single center

Abstract: Aims To investigate the predicted factors influencing the outcomes in acute ischemic stroke (AIS) patients who received tirofiban after endovascular treatment (EVT) and the optimal administration of tirofiban. Methods In this retrospective study, AIS patients who received EVT followed by tirofiban between January 2017 and October 2021 were enrolled. The dose and duration of tirofiban were adjusted by trained clinicians according to the patient's clinical status. A reduction of at least four points on the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…This approach would enable the identification of patients who are more likely to experience bleeding complications and facilitate the implementation of appropriate risk mitigation strategies. However, studies by X. Pan et al and Y. Wang et al provide conflicting results regarding the safety of tirofiban in endovascular stroke treatment [ 12 , 22 ]. X. Pan et al evaluated the safety and efficacy of tirofiban as adjunctive therapy in patients with acute vertebrobasilar artery occlusion undergoing mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach would enable the identification of patients who are more likely to experience bleeding complications and facilitate the implementation of appropriate risk mitigation strategies. However, studies by X. Pan et al and Y. Wang et al provide conflicting results regarding the safety of tirofiban in endovascular stroke treatment [ 12 , 22 ]. X. Pan et al evaluated the safety and efficacy of tirofiban as adjunctive therapy in patients with acute vertebrobasilar artery occlusion undergoing mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients outside the thrombolytic time window, there is currently no better treatment option. Studies have shown that tirofiban is an effective treatment for acute ischemic stroke and it is beneficial for the recovery of neurological function [4].…”
Section: Introductionmentioning
confidence: 99%